Three-Dimensional Neutronic Calculations for the Fusion Breeder APEX Reactor - Korkmaz, M. E.; Sarer, B.; Hancerliogullari, A.; Guenay, M. (Informa UK Limited, 2007)
Three-dimensional analysis has been made using the MCNP Monte Carlo code and ENDF/B-VI nuclear data. The nuclear characteristics of a fusion-fission hybrid reactor such as tritium breeding ratio, energy multiplication factor, fissile fuel breeding, first wall radiation damage, and heat deposition have been investigated in a liquid first wall, blanket, and shield for the various mixture compositions of molten salt and heavy metals for blanket layer thicknesses of 20, 30, 40, and 50 cm. The neutron flux load at the first wall is assumed to be 10 MW/ m 2 . The flowing molten salt wall is composed of flibe (Li 2 BeF 4 ) as the main constituent with increased mole fractions of heavy metals, 2 to 10% ThF 4 and UF 4 . In terms of all parameters, the mixtures with UF 4 show better performance than the mixtures with ThF 4 . The atomic displacement and the helium, tritium production rates remain well below the presumable limits for all mixture compositions of molten salt and heavy metals and thicknesses of the blanket.
Keywords: 7. Clean energy